Biology, population dynamics and management of carpenter (Argyrozona argyrozona) an endemic South African reef fish - Brouwer, Stephen Leonard (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2005)
Carpenter, Argyrozona argyrozona (Valenciennes, 1830), is an endemic South African sparid fish. They form an important component of the commercial linefishery on the South African east coast, where they are the third most important species landed. Recent investigations revealed that the catch per unit effort (cpue) of this species has declined markedly since the early 1900's. Despite these declines and the importance of this resource, remarkably little biological information on this species exists for providing management advice. This thesis investigates the life history of carpenter, particularly those aspects that are used for management. This includes an investigation into the stock distribution and identification of nursery areas, and an assessment of age, growth, reproduction and movement patterns. Age and growth was assessed using methods based on both otoliths and mark-recapture. Transverse sagittal sections from the Tsitsikamma National Park showed clear opaque and translucent growth increments. Marginal growth zone analysis and mark-recapture of chemically tagged fish (Oxytetracycline) revealed that these were deposited on an annual basis: opaque in summer and translucent in winter. A. argyrozona were found to be long lived (up to 27 years) and slow growing. Within reader (between counts) and between readers average percent error (APE) was 5.3 and 1.8, respectively, showing that readability of carpenter otoliths is high. Comparison between whole and sectioned otoliths showed that the former significantly under-estimated the age of fish older than 10 years (p<0.01). A large proportion (68%) of the individual growth rates derived from mark-recapture data were below those predicted by the otolith based von Bertalanffy growth model (p<0.01). This was attributed to the negative influence of external tags, as hydroids, frequently occurring on the tags of recaptured fish, were observed to cause severe lesions and in some cases, extensive fin damage. This brings into question the use of mark-recapture studies to calculate growth of some species. The effects of sampling design and sample size on age and growth estimation were assessed. The minimum sample size required to accurately estimate growth and mortality, and the effects of using either random or stratified sampling procedures were tested. Decimal and integer ageing both produced similar estimates of von Bertalanffy growth parameters, growth curves, spawner biomass-per-recruit (SB/R) and fishing mortality (F) estimates. Sampling monthly throughout the year and collecting data in a single large sample provided similar growth curves, von Bertalanffy, F and SB/R estimates. The data showed that estimates based on less than 300 random samples were unreliable. However, accurate growth parameter estimates were achievable with less than 200 samples if the sample was stratified with 10 or more samples per 2 cm size class. An investigation into the reproductive biology of A. argyrozona within the Tsitsikamma National Park revealed that they were serial spawning late gonochorists. The size at 50% maturity (Lâ‚…â‚€) was estimated at 292 and 297 mm FL for females and males, respectively. Both monthly gonadosomatic indices and macroscopically determined ovarian stages strongly suggest that A. argyrozona within the Tsitsikamma National Park spawn in the austral summer between November and April. The presence of post-ovulatory follicles (POF's) confirmed the six month spawning season, while monthly proportions of early (0-6 hour old) POF's showed that spawning frequency was highest (once every 1-2 days) from December to March. Although spawning season was more highly correlated to photoperiod (r = 0.859) than temperature (r = -0.161), the daily proportion of spawning fish was strongly correlated (r = 0.93) to ambient temperature over the range 9-22â °C. Both spawning frequency and season increased with fish length. As a result of the allometric relationship between annual fecundity and fish mass a 3 kg fish was calculated to produce 5 fold more eggs per kilogram of body weight than a fish of 1 kg. In addition to producing more eggs per unit weight each year, larger fish also produce significantly larger eggs. Adult emigration and larval dispersal of A. argyrozona from the Tsitsikamma National Park (TNP), South Africa, were investigated using mark-recapture data and Acoustic Doppler Current Profiler measurements of currents. Tagging data showed that adult carpenter were mainly resident, with a small proportion (7%) leaving the TNP in both easterly and westerly directions. No relationship was found between fish movement patterns and fish size or time-at-liberty. Current patterns suggest that eggs and larvae spawned within the TNP are mainly transported eastwards towards established nursery grounds; the median estimated distance moved was 299 km (range 42-561 km) in 30 days (time to flexion). Given this pattern of ichthyoplankton dispersal together with the fact that adult carpenter within the TNP display a high degree of residency and that they are much more abundant than in adjacent fishing grounds (cpue = 23 times greater), it appears that the TNP protects a viable carpenter spawner population capable of seeding adjacent fishing grounds. Fishery independent biomass surveys and commercial linefish catch returns were used to elucidate the spatial patterns of A. argyrozona distributed along the South African continental shelf. Two distinct areas of abundance were determined, one on the central and the other on the eastern Agulhas Bank. Tagging studies revealed little exchange between them. Two distinct nursery areas were identified. These data suggest that in each area juvenile A. argyrozona settle and move inshore, and then move offshore as they grow. Otolith readability and growth rates varied between regions, with fish from the Eastern Cape having the lowest average percentage error and the slowest growth rates, readability decreased westward. Lâ‚…â‚€ varied between the central and eastern Agulhas Bank as did mass at length. Based on the distribution of carpenter, variability in otolith readability, mass at length, variation in growth and size at maturity, it is concluded that carpenter exist as two separate stocks, one on the central Agulhas Bank and the other on the eastern Agulhas Bank. SB/R, fecundity-per-recruit (Egg/R) and yield-per-recruit (Y/R) models were used to model both South African carpenter stocks. Owing to the allometric relationship between annual fecundity and individual size, Egg/R ratios were between 40 and 74% of SB/R at equivalent F. Egg/R ratios account for allometric increases in fecundity with size/age, and are therefore regarded as more accurate estimates of reproductive potential, and biological reference points for per-recruit analysis should wherever possible be based on this quantum. It is shown that the current length at first capture (lc) (250 mm TL) and F (at M = 0.1) will reduce Egg/R to 6.41% of the pristine value in the Eastern Cape and between 6.06 and 14.15% on the central Agulhas Bank, indicating that both stocks are heavily over exploited. An increase in lc from 250 to 350 mm TL and a 70% reduction in commercial fishing effort is recommended to attain a target reference point of 40% Egg/RF=0. Bag frequency analysis indicates that a reduction in daily bag limit from 10 to 4 fish.personÂ¹.dayâ »Â¹ would effect an equivalent reduction in recreational F. The trawl bycatch of carpenter is only 3% of the reported line catch, consequently restrictions to this fishery are not recommended.
Keywords: Reef fishes -- South Africa; Sparidae -- South Africa